PEDOSTRATIGRAPHY, PEDOLOGICAL AND GEOCHEMISTRY OF KASHMIR LOESS: IMPLICATIONS FOR CHEMICAL WEATHERING HISTORY AND PALEOCLIMATIC RECONSTRUCTION - Chandra, Rakesh; Ahmad, Ishtiaq (European Scientific Journal, ESJ, 2013)
Integrated pedological and geochemical study of the Quaternary Loess-Paleosols sediments of the Kashmir Valley was carried out in order to reconstruct their chemical weathering, paleoclimatological conditions and source. Pedological and micromorphic features of these paleosols indicate that these are weak to moderately developed. It also indicates that both loess deposition and pedogenic processes were taking place simultaneously during either phase of the loess/soil formation. These sediments are generally enriched with Fe2O3, MgO, MnO, TiO2, Y, Ni, Cu, Zn, Th, Sc, V and Co while contents of SiO2, K2O, Na2O, P2O5, Sr, Nb and Hf are lower than the UCC. Al2O3 is slightly higher than the UCC. However, CaO and U show large variations. Rb is generally similar to UCC whereas Ba is slightly lower than the UCC. Chondrite normalized REE patterns are characterized by moderate enrichment of LREEs, relatively flat HREE pattern (GdCN/YbCN = 1.93 to 2.30) and lack of prominent negative Eu anomaly (Eu/Eu* = 0.73 to 1.01, average = 0.81). The weathering indices suggest that these sediments are experiencing weak to moderate degree of weathering and not subjected to potash metasomatism. On the basis of these proxies it is inferred that the climate of Kashmir Valley for the recent past fluctuated between cold arid to warm semi-arid.